Práticas educativas no ensino de Ciências realizadas no âmbito do PIBID: possibilidades e expectativas - Rosalin, Ana Carolina (Universidade Federal de São Carlos, 2022)
The Institutional Scholarship Program for Teaching Initiation (PIBID) emerged as an initiative to improve and enhance teacher training for basic education, establishing a partnership between Higher Education Institutions and Basic Education schools in the public education network. . Currently, the program is the subject of numerous studies that seek to highlight its importance in the initial training process; however, few works deal with the importance and relevance of the practices adopted by PIBID in Basic Education, more specifically in Science Teaching. This research has the general objective of identifying, in theses and dissertations, the educational practices in Science teaching carried out within the scope of PIBID. In this sense, we seek to answer the following research questions: “What practices are prioritized by PIBID in the area of ​​Science teaching? Where do they occur? How do they occur? The pedagogical practices adopted by PIBID, in Science teaching, mostly fit into which pedagogical models?” The present work uses a qualitative approach, where new information was produced regarding practices in the context of PIBID. It is a descriptive research, because it describes the facts and phenomena of the reality in which the educational practices in the teaching of Sciences carried out within the scope of PIBID are inserted. As for the procedures, it is a bibliographical research, using theses and dissertations as a source of data. The data obtained from reading the dissertations and theses were treated using Discursive Textual Analysis (DTA), as it allows understanding the meanings that the participants have about the aspects under study. We analyzed 16 works (13 dissertations and 3 theses) that showed the following aspects: the fulfillment of the current demands of science teaching by PIBID, in joint work with the school; the possibility for scholarship holders to follow everyday school situations and reflect on them based on discussions that emerge at the university; the possibility of continuing education by supervising professors, through activities developed by pibidians, which can provide theoretical subsidies and arouse interest on the part of supervising professors to incorporate them into their practices, in addition to the possibility of incorporating alternatives for teaching the contents proposed in the day-to-day activities of supervising professors, thus producing a positive and collaborative impact.
Educational practices in Science teaching carried out within the scope of PIBID: possibilities and expectations
Keywords: PIBID; Práticas pedagógicas; Formação de professores; Ensino de ciências; Pedagogical practices; Teacher training; Science teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM